2021
DOI: 10.1037/gdn0000134
|View full text |Cite
|
Sign up to set email alerts
|

Deepening the group training experience: Group cohesion and supervision impact in alliance-focused training.

Abstract: The aim of the current study is to explore experiences of trainees engaged in alliance-focused training (AFT), a group supervision modality with an explicit focus on awareness of ruptures and implementation of repair strategies. Using cognitive behavioral therapy (CBT) group supervision as a point of comparison, the study examines supervisory alliance, ruptures, group cohesion and safety, and supervision impact. Method: Eighty-three trainees (clinical psychology interns, advanced-level psychology externs and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…It is also important to research the impact of the type of group treatment being provided. One would imagine that there might be more ruptures in interpersonal process groups compared to more structured cognitive-behavioral groups, as suggested by the findings of Urmanche et al (2021).…”
Section: Group Factors Influencing Rupture and Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to research the impact of the type of group treatment being provided. One would imagine that there might be more ruptures in interpersonal process groups compared to more structured cognitive-behavioral groups, as suggested by the findings of Urmanche et al (2021).…”
Section: Group Factors Influencing Rupture and Repairmentioning
confidence: 99%
“…Most of the ruptures were between supervisees and were similar to the ones experienced by clients in psychotherapy. Urmanche et al (2021) explored the experiences of trainees who were in AFT group supervision and compared them to students in a cognitive-behavioral therapy (CBT) group supervision. Using 83 trainees, they found that trainees in AFT experienced less safety, smoothness, and greater intergroup conflict compared to trainees in the CBT supervision.…”
Section: Marmaroshmentioning
confidence: 99%
See 1 more Smart Citation
“…Otra modalidad de supervisión grupal es entre pares, sin supervisor, y ha permitido la comprensión de aspectos multiculturales de los casos clínicos (Somerville et al, 2019). Por su parte, Urmanche et al (2021) establecieron comparaciones entre la supervisión grupal centrada en las terapias cognoscitivo-conductuales y las centradas en el apego.…”
Section: Técnicasunclassified
“…Otro concepto en esta categoría es el estilo de apego en la relación entre la persona supervisora y supervisada, estudiando cómo el apego del supervisado predice la relación de supervisión después de la retroalimentación crítica de un supervisor (McKibben & Webber, 2017). Así mismo, se han estudiado las rupturas en la alianza entre supervisor y supervisado, encontrando que puede afectar la seguridad, la tranquilidad y el conflicto intergrupal (Urmanche et al, 2021).…”
Section: Relación Supervisor-supervisadounclassified